Analysis of Community and Local Politics The Challenge of the Horizontal Conflict (A Case Study in Kampar Riau, A Constructive Critical Thinking from the Perspective of Political Anthropology) - Syafrizal (Budapest International Research and Critics University, 2021)
This paper wants to critically explain constructively from the perspective of political anthropology, namely one thought on one of the social realities that develop in society Kampar Riau. Society is a group of people who live in one area for a certain period of time, who have emotional attachments and have a common goal. In that context, it is not uncommon for people to incarnate themselves into various situations, including in terms of politics and society. The phenomenon of folklore and local politics is a form of democratic life that is guaranteed by the laws of the Indonesian state. Everyone has their own life history. Talking about humans would be tantamount to talking about who is the owner and creator of all cultures. Humans create their experiences since childhood in the environment in which they were born. Community phenomenon is one of the oldest that characterizes a person's attitude, behavior pattern, which consciously or unconsciously will be incarnated in the long process of his life wherever that person takes part as an adult, such as taking part in an organization, company, or in a certain political party.